Social Deixis in the Novel â€œGadis Pesisirâ€ By Nunuk Y. Kusmiana Pragmatic Review - Ulina Beru Ginting, Sri; Hayati Maulidiah, Rina; Nisa, Khairun (Green Publisher, 2022)
This study aims to describe the form of social deixis in the novel Gadis Pesisir by Nunuk Y. Kusmiana with a pragmatic review. The research approach used in this study uses a qualitative approach with descriptive analysis techniques. This research is a qualitative research with a descriptive method that examines social deixis in an Indonesian novel with a pragmatic review. The data collection technique used is literature study. The data sources in this study are primary data and secondary data, the primary data used researchers in research are sentences or paragraphs that have social deixis in the novel